Assessment of the psychometric properties of the Indonesian version of the General Self-Efficacy Scale-12 (GSES-12) in a sample of Indonesian high school students - Soetjipto, Helly Prajitno; Putra, Muhammad Dwirifqi Kharisma; Widhiarso, Wahyu; Khakim, Zulfikri (Psikohumaniora: Jurnal Penelitian Psikologi, 2023)
In recent decades, self-efficacy has been one of the major subjects of interest in the field of psychology, with numerous studies published on the topic. This study aims to examine the psychometric features of the General Self-Efficacy Scale-12 (GSES-12), a widely used instrument for assessing general self-efficacy. The Indonesian adaptation of the GSES-12 was validated using item factor analysis (IFA). The study involved a total of 584 high school student participants (M-age = 16.02, SD-age = 1.39; boys = 266, girls = 318). The results obtained from the IFA indicate that the psychometric properties of the GSES-12 were satisfactory. The results exhibited a strong fit with the second-order IFA models and all items had statistically significant factor loadings. In addition, the results obtained from the multigroup IFA indicate that the configural invariance testing models exhibited a satisfactory level of goodness-of-fit (RMSEA < 0.06, CFI & TLI > 0.90). These findings suggest that there were no differences between the genders in the factor structure of the GSES-12.